Polygenic risk of prediabetes, undiagnosed diabetes, and incident type 2 diabetes stratified by diabetes risk factors - Liu, X; Collister, JA; Clifton, L; Hunter, DJ; Littlejohns, TJ (Oxford University Press, 2023)
Context: Early diagnosis of type 2 diabetes is crucial to reduce severe comorbidities and complications. Current screening recommendations for type 2 diabetes include traditional risk factors, primarily body mass index (BMI) and family history, however genetics also plays a key role in type 2 diabetes risk. It is important to understand whether genetic predisposition to type 2 diabetes modifies the effect of these traditional factors on type 2 diabetes risk.